Stress contagion in school: A multiverse analysis of social influence on school-related stress - Björn Högberg; Cristian Bortes (PLoS ONE, 2026)
Introduction Studies have found that behaviors, beliefs, and emotions can be socially contagious and spread between students. Qualitative research suggests that this may apply to school-related stress as well, but quantitative evidence remains limited and potentially sensitive to methodological choices. This study investigated (1) whether individual students’ school-related stress is influenced by their classmates’ stress, and (2) to what extent estimates of such influence vary depending on different methodological choices. Methods Panel data from two cohorts of Swedish secondary school students (51.7% girls; M age wave 1 = 13.0, SD = 0.18; M age wave 2 = 16.0, SD = 0.19) were used. Data were analyzed using multiverse analysis, systematically varying the type of statistical model (unit fixed effects, lagged dependent variable, prospective cohort, and school fixed effects models), measurement of stress (continuous vs. dichotomized), operationalization of classmates’ stress, sample restrictions, and control variables. Results Of 9,240 model specifications, approximately 80% yielded positive stress contagion effects. However, these were generally small (standardized effects: 0–0.15; odds ratios: 1–1.2) and mostly non-significant, and the size as well as sign of the effects varied substantially across model types. Conclusions The findings suggest that stress appears to be driven primarily by other factors that may cluster within schools or classes but that contagion per se is probably less important. Reducing school-related stress requires direct intervention focused on concrete and institutional stressors in school rather than targeting direct interpersonal stress transmission. The overall fragility of the estimated contagion effects underscores the importance of methodological transparency and systematic robustness analyses.